Effect of the Use of Quail Hatchery Waste on the Live Weight and Percentage of Male Quail Carcass (Coturnix coturnix japonica) - Ardian Ozzy Wianto; Astari Ratna Duhita (Bantara Journal of Animal Science, 2022)
The study aims to find out the life weight and percentage of carcass of male quails due to the use of quail egg hatchery waste on rations. The material used in this study was 90 male quail (Coturnix coturnix japonica) aged 4 weeks with an average body weight of 60 ± 4.02 grams. Quails were kept in colony cages with walls made of ram wire lined with cardboard and on the bottom using ram wire. The size of the cage is 50 x 25 x 25 cm as many as 15 cage units, each cage unit is equipped with a feed and drinking place and a 25 watt lamp for lighting. The observed parameters are the live weight and carcass percentage.  The treatment tried is T0 = basal ration without hatchery waste, T1 = Use of hatchery waste 9% in rations, T2 = Use of hatchery waste 12% in rations. The results showed that the use of hatchery waste of 0%-12% in rations had no real effect on carcass production. It could be conclude that the use of quail hatchery waste can be used up to 12% without adversely affecting life weights and carcass percentage.Keywords: carcass percentage, hatchery waste, life weight